Influence of unwanted thoughts about other people on drivers' attention processes - Piotr Makowiec (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
The author of this paper is interested in the significance of the emergence of unwanted automatic thoughts in the form of stereotypes for the attention abilities of drivers.